Organisational design for an integrated oncological department - Ch.L. Meiss-de Haas; H. Falkmann; J. Douma; J.G. van Gassel; W.G. Peters; R. van Mierlo; J.M. van Turnhout; C.A.H.H.V.M. Verhagen; A.J.P. Schrijvers (International Journal of Integrated Care, 2001)
Objective: The outcomes of a Strength, Weakness, Opportunities and Threat (SWOT) analysis of three Integrated Oncological Departments were compared with their present situation three years later to define factors that can influence a successful implementation and development of an Integrated Oncological Department in- and outside (i.e. home care) the hospital. Research design: Comparative Qualitative Case Study. Methods: Auditing based on care-as-usual norms by an external, experienced auditing committee. Research setting: Integrated Oncological Departments of three hospitals. Results: Successful multidisciplinary care in an integrated, oncological department needs broad support inside the hospital and a well-defined organisational plan.